The Effect of Reducing Information Asymmetry on Loan Price and Quantity in the African Banking Industry - Simplice Asongu (African Governance and Development Institute (AGDI), 2017)
The purpose of this study is to assess how information sharing offices affect loan price and quantity in the African banking industry. The empirical evidence is based on a panel of 162 banks in 42 countries for the period 2001-2011. From the Generalised Method of Moments, public credit registries decrease loan price. With instrumental Quantile Regressions, two main findings are established. Public credit registries consistently decrease the price of loans whereas private credit bureaus consistently have the opposite effect. Public credit registries increase loan quantity in bottom quintiles (or banks associated with lower loan quantities) while private credit bureaus increase loan quantity in top quintiles (or banks associated with higher loan quantities).
Keywords: G20; G29; O16; O55; 330; Information Asymmetry; Financial Access; Africa